POTENSI AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL BUNGA ASOKA (Ixora coccinea L.) - Ramadhan, Aulia; Saleh, Chairul; Hairani, Rita; Ruga, Ritbey (Jurusan Kimia FMIPA UNMUL, 2024)
Extraction of asoka (Ixora coccinea L.) flowers, phytochemical screening, and antioxidant activity of methanol extract of asoka flowers have been conducted. This study aimed to determine the content of secondary metabolites in the methanol extract of asoka flowers and its antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The phytochemical screening test revealed that the methanol extract of asoka flowers contained secondary metabolites such as flavonoids, alkaloids, triterpenoids and saponins. With 1 mg/mL, the methanol extract exhibited potential as an antioxidant with an inhibition percentage of 88.10% while vitamin C as a standard used in this study at 1 mg/mL showed an antioxidant activity of 99.23%.